Peran Guru dalam Membentuk Karakter Disiplin Siswa melalui Penguatan Literasi Digital di SDN 2 Selat Penuguan - Carsim Carsim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe teachers’ roles in shaping students’ disciplinary character through the strengthening of digital literacy at SDN 2 Selat Penuguan, identify the obstacles faced by teachers, and formulate efforts to overcome those obstacles. The study is significant because primary education is not only oriented toward cognitive achievement but also toward character formation, particularly discipline, amid rapid digital development. This research employed a descriptive qualitative approach involving the principal, teachers, and students as data sources. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data display, conclusion drawing, and verification. Data trustworthiness was strengthened through source and technique triangulation. The findings indicate that teachers play roles as educators, role models, mentors, facilitators, supervisors, motivators, and evaluators in cultivating students’ discipline through digital literacy activities. Digital literacy strengthening was carried out through the use of simple learning media, guidance on ethical technology use, habituation of timely task completion, and supervision of students’ digital learning behavior. The main obstacles included limited facilities, unstable internet access, variations in teachers’ and students’ digital competencies, and uneven parental involvement. Teachers’ efforts included digital discipline habituation, school-parent collaboration, the use of offline learning resources, and reinforcement of classroom rules.